Acercamiento al Pacto Educativo Global (2021)
Talking about the Global Educational Pact implies deepening the thought of Pope Francis, the genesis and the consequences of a truly revolutionary proposal. That is why I am going to make my presentation in a small "Decalogue" of three sections, each of them tripartite, which I have called "Text", "Context" and "Posttext" (the latter as a kind of neologism that projects the text and its context into the future). In the last part, the conclusion, I will refer to its implications for theological work. Following the scholastic method, I will begin this first part with a necessary clarification of terms.